Existence and uniqueness of weak solutions for a system applied to image decomposition. Issue 16 (10th December 2018) - Liu, Qiang; Gao, Tianling; Xia, Li
ABSTRACT: In this paper, we prove the existence and uniqueness of weak solutions for a singular evolutionary system, which is deduced from a model for image decomposition combining staircase reduction and texture extraction. The main method we used is p -Laplace regularization. The numerical experimental result shows the efficiency of this kind of model.